Affecting of aquatic vascular plant Lemna minor by cisplatin revealed by voltammetry - Supalkova, Veronika; Beklova, Miroslava; Baloun, Jiri; Singer, Christoph; Sures, Bernd; Adam, Vojtech; Huska, Dalibor; Pikula, Jiri; Rauscherova, Libuse; Havel, Ladislav; Zehnalek, Josef; Kizek, Rene (Bioelectrochemistry (Amsterdam, Netherlands), 2008)
Within the context of application of platinum derivates based effective cytostatics, we can suppose that these risk metals can get into aquatic ecosystems where they can show biologic availability for food chain. In the present work we report on investigation of affecting of duckweed (Lemna minor) by various doses of cisplatin (0, 5, 10, 20, 40, 80 and 160 microM) for 4 days. The toxic influence of cisplatin was evaluated on the basis of growth inhibition expressed as number of leaves, growth rate, and total amount of biomass. The result value of 96hEC50, calculated from growth inhibition with comparison of growth rates, was 6.93 microM. Moreover we aimed on determination of cisplatin content using differential pulse voltammetry. The highest content of cisplatin (320 ng g(-1) of fresh weight) was determined in plants treated by 80 microM at the second day of treatment. Plants protect themselves against heavy metals by means of synthesis of cysteine-rich peptides such as glutathione and phytochelatins. Thus thiol determination in the treated plants by means of Brdicka reaction followed. The marked increase in thiol concentration detected is associated with defence reaction of the plant against stress caused by cisplatin.
Keywords: Electrochemistry; ekosystém; voda; Biodegradation, Environmental; Ecosystem; Water Pollution, Chemical; vztah mezi dávkou a účinkem léčiva; cisplatina; Water; Dose-Response Relationship, Drug; sulfhydrylové sloučeniny; biodegradace; Araceae; chemické znečištění vody; Cisplatin; Sulfhydryl Compounds; elektrochemie